Clinical Utility of Simultaneous Quantitation of 25-Hydroxyvitamin D and 24,25-Dihydroxyvitamin D by LC-MS/MS Involving Derivatization With DMEQ-TAD - Kaufmann, Martin; Gallagher, J. Christopher; Peacock, Munro; Schlingmann, Karl-Peter; Konrad, Martin; DeLuca, Hector F.; Sigueiro, Rita; Lopez, Borja; Mourino, Antonio; Maestro, Miguel; St-Arnaud, René; Finkelstein, Joel S.; et al. (The journal of clinical endocrinology and metabolism, 2014)
Context:The discovery of hypercalcemic diseases due to loss-of-function mutations in 25-hydroxyvitamin D-24-hydroxylase has placed a new demand for sensitive and precise assays for 24,25-dihydroxyvitamin D [24,25-(OH)2D].Objective:We describe a novel liquid chromatography and tandem mass spectrometry-based method involving derivatization with DMEQ-TAD {4-[2-(6,7-dimethoxy-4-methyl-3,4-dihydroquinoxalinyl)ethyl]-1,2,4-triazoline-3,5-dione} to simultaneously assay multiple vitamin D metabolites including 25-hydroxyvitamin D (25-OH-D) and 24,25-(OH)2D using 100 μL of serum with a 5-minute run time.Design:The assay uses a newly synthesized internal standard d6-24,25-(OH)2D3 enabling the quantitation of 24,25-(OH)2D3 as well as the determination of the ratio of 25-OH-D3 to 24,25-(OH)2D3, a physiologically useful parameter.Setting:We report data on more than 1000 normal and disease samples involving vitamin D deficiency or hypercalcemia in addition to studies involving knockout mouse models.Results:The assay showed good correlation with samples from quality assurance schemes for 25-OH-D (25-OH-D2 and 25-OH-D3) determination (−2% to −5% bias) and exhibited low inter- and intraassay coefficients of variation (4%–7%) and lower limits of quantitation of 0.25–0.45 nmol/L. In clinical studies, we found a strong correlation between serum levels of 25-OH-D3 and 24,25-(OH)2D3 (r2 = 0.80) in subjects over a broad range of 25-OH-D3 values and a marked lack of production of 24,25-(OH)2D3 below 25 nmol/L of 25-OH-D. The ratio of 25-OH-D3 to 24,25-(OH)2D3, which remained less than 25 in vitamin D-sufficient subjects (serum 25-OH-D < 50 nmol/L) but was greatly elevated (80–100) in patients with idiopathic infantile hypercalcemia.Conclusions:The new method showed good utility in clinical settings involving vitamin D deficiency; supplementation with vitamin D and idiopathic infantile hypercalcemia, as well as in animal models with ablation of selected cytochrome P450-containing enzymes involved in vitamin D metabolism.